The impact of early amplification on the social development of children with hearing loss - Dubravka Pralica (Биомедицинска истраживања, 2025)
Introduction: Early amplification in children with hearing impairment plays a crucial role in their socioemotional and communicative development. Timely identification and intervention are essential to support better outcomes in communication, socialization, and emotional well-being. This study aimed to examine whether children who received hearing amplification before the age of three show better socialization outcomes compared to those amplified after the age of three. Methods: The study involved 52 parents of children, aged between 7 and 11 years with hearing impairment, who completed a specially designed Likert-type questionnaire. The questionnaire consisted of three subscales:Communication, Socialization, and Emotional Stability. The age at which amplification was provided varied: 12 children (23%) received amplification during the first year of life, 17 (33%) during the second year, 13 (25%) during the third year, and 10 children (19%) during the fourth year. In most cases (22 children, or 42%), hearing loss was detected during the second year of life. Results: Children who received amplification before the age of three demonstrated significantly better outcomes in socialization compared to those amplified after the age of three. Additionally, better social interaction in these children was associated with stronger verbal communication skills and greater emotional stability. Conclusion: The findings emphasize the importance of early detection and timely amplification in children with hearing impairments. Amplification provided by the age of three leads to improved socialization, communication, and emotional development, thereby enhancing the overall quality of life for affected children.
Keywords: hearing impairment; early amplification; socialization